Reúso pragmático de neumáticos en un proyecto educativo para alcanzar competencias del desarrollo sostenible - Guevara Sáenz de Viteri, Jéssica (2020)
Applies philosophical pragmatism current combining Sustainable Development Objectives Competences: Self-awareness of environmental value in order to contribute with NFU Reuse forms integrated to collaborative work in (PEI) Institutional Educational Project Land of Children and Adolescents (TINI); as a curricular requirement in medium-level educational units in Ecuador contributing to the improvement of the environment. The Tire Reuse Program of the Ministry of Industries and Productivity Ecuador, estimated that 300 thousand tires are destined to dumps or other sites and after the execution of the TINI recovered approximately 2% serving the ornament of the units under investigation. Bartlett's test was applied, whose significance is (P <0.01), which allowed rejecting the null hypothesis that the correlation matrix is ​​equal to the identity matrix, and it is concluded that there is indeed an association between the original variables and a reduction dimensional activities of the educational project of pragmatic reuse of used tires, considered as special waste in Ecuador. Environmental pragmatism gives rise to the formation of multipliers achieving significant changes in the habit of reusing special waste, as well as the promotion of collaborative work and stimulation of creativity; achieving environmental awareness.